Pengaruh Produksi dan Harga Kopi Dunia terhadap Daya Saing Ekspor Biji Kopi Indonesia - Fadlul Oktavian; Arief Maulana (Jurnal Kajian Manajemen dan Wirausaha, 2019)
Purpose - The purposes of this researches are to analyze: (1) The effect of production of coffee beans toward the competitiveness of Indonesian Coffee Export, (2) The effect on International Coffee Price toward the competitiveness of Indonesian Coffee Export.   Methodology - The population in this study is the activities of the export coffee in Indonesia during last 31 years. The sample used is a sample of total coffee production and world coffee prices. Data type that used is a secondary data that formatted using SPSS 21. Finding - The results of this study indicate that: (1) There is a positive and non-significant influence between total production and the competitiveness of exports of Indonesian coffee beans (2) There is a Positive and Significant influence between the World Coffee Prices and the Competitiveness of Indonesian Coffee Beans.   Keywords: Production, Price, Competitiveness